1976
DOI: 10.1111/j.1365-2141.1976.tb00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Blast Crisis of Chronic Myeloid Leukaemia (CML): II. CELL SURFACE MARKER ANALYSIS OF ‘LYMPHOID’AND MYELOID CASES

Abstract: Fourteen cases of philadelphia chromosome (Ph1) positive chronic myeloid leukaemia in blast transformation have been investigated using cell surface markers. Morphologically eight cases were lymphoid and the remainder myeloid in appearance. All cases were negative with surface markers for thymocytes and T and B lymphocytes. Five of the lymphoid cases reacted with an antiserum specific for acute lymphoid leukaemia )ALL) of non-T non-B type and were also weakly reactive with a lymphocyte reactive antiserum. A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2

Year Published

1977
1977
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(36 citation statements)
references
References 26 publications
3
31
2
Order By: Relevance
“…Finally, antigens present on immature members of the human B-cell lineage have also been identified on K562 cells (25), and some anti-K562 cell antibodies react with transformed B cells. These results support a B-cell origin for the blast cells ofchronic myelogenous leukemia in crisis (26) and the common origin of B lymphocytes and hematopoietic progenitors.…”
Section: Methodssupporting
confidence: 76%
“…Finally, antigens present on immature members of the human B-cell lineage have also been identified on K562 cells (25), and some anti-K562 cell antibodies react with transformed B cells. These results support a B-cell origin for the blast cells ofchronic myelogenous leukemia in crisis (26) and the common origin of B lymphocytes and hematopoietic progenitors.…”
Section: Methodssupporting
confidence: 76%
“…Usually, blast crisis (BC) in chronic granulocytic leukaemia (CGL) proves to be refractory to treatment protocols used in acute myelogenous leukaemia [1], How ever, about one-third of the patients may be successfully treated with vincristine (V) and prednisolone (P) [2], Their leukaemic blasts have morphological and immuno logical characteristics in common with acute lymphoblastic leukaemia of com mon type (c-ALL) [3,4], We describe a pa tient with Philadelphia chromosome-posi tive (Ph'+) CGL who experienced recur rent blast crises and a meningeal relapse. His leukaemic blasts showed varying ex pression of lymphoid and/or myeloid (myelomonocytic) phenotype during the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…or the in volvement of closely related target cells [8]. However, it must be pointed out that anti-ALL antisera as those employed in the above mentioned and other studies [2,9,10,16] are claimed to be directed against leukae mia-associated antigens and, because of proper absorptions with peri pheral blood lymphocytes, do not react with B or T cells. In other words ALL antisera should be devoid of antibodies capable of recognizing dif ferentiation antigens expressed on both mature and immature lymphoid (LY) cells, but only leukaemia-associated antigens or other determinants, restricted to that particular stage of differentiation, should react with such antisera.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the agranular blasts have failed to prove their B or T nature by means of common sur face markers [8,15]. Most recently Janossy et al [8,9] have reported that the blast cells of some cases of CML-lyBC strongly react with hetero antisera specific for ALL-associated antigens, suggesting that acute lym phoblastic leukaemia (ALL) and CML-lyBC either involve the same aetiological agent or the same target cell [8].…”
mentioning
confidence: 99%